2022
DOI: 10.1021/acs.jafc.2c06187
|View full text |Cite
|
Sign up to set email alerts
|

ROS Stress and Cell Membrane Disruption are the Main Antifungal Mechanisms of 2-Phenylethanol against Botrytis cinerea

Abstract: 2-Phenylethanol (2-PE), a common compound found in plants and microorganisms, exhibits broad-spectrum antifungal activity. Using Botrytis cinerea, we demonstrated that 2-PE suppressed mycelium growth in vitro and in strawberry fruit and reduced natural disease without adverse effects to fruit quality. 2-PE caused structural damage to mycelia, as shown by scanning and transmission electron microscopy. From RNA sequencing analysis we found significantly upregulated genes for enzymatic and nonenzymatic reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Recently, numerous natural antifungal compounds, such as linalool, phytic acid, 2-phenylethanol, thymol, and salicylic acid, have been reported to induce the accumulation of reactive oxygen species (ROS) in fungi, which could disrupt the imbalance in cellular redox homeostasis and ultimately lead to fungal cell death. In contrast, 2,4-DTBP was reported to be able to inhibit ROS production in both Aspergillus and Phytophthora cinnamomic, also resulting in an impact on cell growth and development, which appeared to be correlated with its antioxidative activity .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, numerous natural antifungal compounds, such as linalool, phytic acid, 2-phenylethanol, thymol, and salicylic acid, have been reported to induce the accumulation of reactive oxygen species (ROS) in fungi, which could disrupt the imbalance in cellular redox homeostasis and ultimately lead to fungal cell death. In contrast, 2,4-DTBP was reported to be able to inhibit ROS production in both Aspergillus and Phytophthora cinnamomic, also resulting in an impact on cell growth and development, which appeared to be correlated with its antioxidative activity .…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O 2 is a typical ROS, acting either as a signal molecule to trigger plant defense responses or as a simulator of oxidative stress to kill pathogens directly, thereby inhibiting the infection process of pathogens. 26,30,31 Our prior study showed that H 2 O 2 content in banana peel was altered during the interactions between F. proliferatum and banana fruit. 1 Hence, in the present study, we chose H 2 O 2 to treat F. proliferatum, which is an important fungus causing banana crown rot during postharvest storage.…”
Section: ■ Discussionmentioning
confidence: 99%
“…During interactions of plants and pathogens, plants generate ROS as an important defense factor. H 2 O 2 is a typical ROS, acting either as a signal molecule to trigger plant defense responses or as a simulator of oxidative stress to kill pathogens directly, thereby inhibiting the infection process of pathogens. ,, Our prior study showed that H 2 O 2 content in banana peel was altered during the interactions between F. proliferatum and banana fruit .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the development of nanopreparations in fungicides could effectively improve the utilization rate, increase the efficacy of the original drug, and reduce the impact on the environment. , In addition, the discovery and fungicidal application of microbial pesticides, natural products, RNA interference, and polypeptides could also meet the needs of green development. − Furthermore, the development of new green ecological fungicides could also delay the increase of pathogen resistance. , Meanwhile, structural modification based on natural products has become an effective way to develop new green agrochemicals, such as natural strobilurin A-derived methoxyacrylate fungicides, natural cinnamic acid-derived dimethomorph, and so on. − At present, although commercial fungicides have various structures, the fungicidal targets are same for the similar structures, which results in the existence of cross-resistance. Therefore, the discovery of new pharmacophores and the exploration of new targets are also very important for the development of fungicides …”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…Therefore, the discovery of new pharmacophores and the exploration of new targets are also very important for the development of fungicides. 107 Hydrazide structures have been reported to have a wide range of biological activities; however, there are no successful commercial examples in the field of agricultural fungicides. In this Review, the fungicidal activities of various hydrazides and their derived structures in the agricultural field are described in order to construct and analyze the SAR.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%